Hubungan Faktor Water, Sanitation, and Hygiene (WASH) dengan Stunting di Wilayah Kerja Puskesmas Kotakulon, Kabupaten Bondowoso - Alfadhila Khairil Sinatrya; Lailatul Muniroh (Amerta Nutrition, 2019)
Background: In 2017 prevalence of stunting in, Indonesia reached 29.6% and Bondowoso District was one of district that contributes the third higher prevalence, amounted 38.3%. One of underlying cause of stunting were water, sanitation and hygiene (WASH).Objectives: This research aims to analyze the correlation between WASH with stunting among children aged 24 - 59 months in working area of Kotakulon Public Health Center, Bondowoso District.Methods: This was an observational analytic study with case-control design. The sample size of this research was 66 children aged 24 to 59 months in working area of Kotakulon Public Health Center, Bondowoso District. This case-control study consisted of 33 children in case group and 33 children sample of contro groupl. The dependent variable was stunting status, while the independent variables were drinking water source, quality of drinking water, the ownership of lathrines, and mother’s handwashing habits. The data were analyzed using chi-square test.Results: Hand washing habit (p<0.001; OR=0.12) was a risk factor of stunting in under-five years old  which has risk 0.12 times higher for mother that has a poor handwashing habit, while drinking water source (p=0.41), quality of drinking source (p=0.58), the ownership of lathrines (p=0.22) were not accunted as a risk of stunting.Conclusions: A poor handwashing habit in mother contribute to stunting in working area of Kotakulon Public Health Center, Bondowoso District.ABSTRAKLatar Belakang: Pada tahun 2017, prevalensi stunting di Indonesia mencapai angka 29,6% dan Kabupaten Bondowoso adalah kabupaten yang menyumbang angka tertinggi ketiga di Jawa Timur yaitu sebesar 38,3% balita stunting. Salah satu penyebab tidak langsung dari stunting adalah faktor water, sanitation, and hygiene (WASH).Tujuan: Penelitian ini bertujuan untuk enganalisis hubungan WASH dengan stunting pada anak usia 24 – 59 bulan di Wilayah Kerja Puskesmas Kotakulon, Kabupaten Bondowoso.Metode: Jenis penelitian adalah observasional analitik dengan desain kasus kontrol. Besar sampel penelitian yaitu 66 balita usia 24 – 59 bulan di wilayah kerja Puskesmas Kotakulon, Kabupaten Bondowoso. Penelitian kasus kontrol ini terdiri dari sampel kasus sebanyak 33 balita yang mengalami stunting dan sampel kontrol sebanyak 33 balita yang tidak mengalami stunting. Variabel dependen adalah kejadian stunting. Variabel independen adalah WASH, meliputi sumber air minum, kualitas fisik air minum, kepemilikan jamban, dan kebiasaan cuci tangan ibu. Data dianalisis menggunakan uji chi-square.Hasil: Kebiasaan cuci tangan (p<0,001; OR=0,12) adalah faktor risiko dari stunting pada balita dengan besar risiko 0,12 kali lebih tinggi bagi ibu yang memiliki kebiasaan cuci tangan kurang baik, sedangkan sumber air minum (p=0,415), kualitas fisik air minum (p=0,58), kepemilikan jamban (p=0,22) bukan merupakan faktor risiko dari stunting.Kesimpulan: Kebiasaan cuci tangan yang buruk pada ibu berkontribusi terhadap kejadian stunting di wilayah kerja Puskesmas Kotakulon Kabupaten Bondowoso.